Analytical and Experimental Study Bamboo Beam Concrete - Hery Riyanto; Sugito SUGITO; . Juli (International Conference on Engineering and Technology Development (ICETD), 2013)
This study is known as the Bamboo Concrete Beams (B3) with bamboo casing as an alternative reinforcement, conducted through experimental methods. The test results were then verified through analytical calculations. Behaviors examined included mechanical properties of bending, beam flexural strength and fracture patterns are burdened by the quasi-static load. Researchers used 16 pieces of the test specimen. Bamboo specimens used in this study is a type of Petung Bamboo (Dendrocalamus Asper), with a long piece of bamboo varies from 2860 mm to 3910 mm, outer diameter of the bottom of the 105 mm to 155 mm and the outer diameter of the upper section of 95 mm to 135 mm, which are grouped into 5 kinds of testing that is,1. Bamboo intact, the inner segments remain, with BA code (2 pieces of the specimen)2. Bamboo intact, the inner segments removed, the code BP (2 pieces of the specimen)3. Bamboo shoots in a section removed (like bamboo pipes) and not given a bamboo rod stud, with code BTS (4 pieces of the test specimen).4. Bamboo shoots in a section removed (like bamboo pipes) and given a bamboo rod stud on the inside along Â½ bamboo inner diameter, with code BAS (4 pieces of the test specimen). 5. One side of the split bamboo rod sections with a thickness of 75 mm, inner bamboo segments remain (such as drums) and given a bamboo rod stud on the inside, with code KTGN (4 pieces of the test specimen). Value of the maximum load Pmax, the maximum moment Mmax and ï´max deflection for each specimen according to the results of observation and calculation is as follows